2018
DOI: 10.1159/000495555
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Morus Root Extract (MRE) Against Lipopolysaccharide-Activated RAW264.7 Cells and CCl4-Induced Mouse Hepatic Damage

Abstract: Background/Aims: Inflammation is one of the main contributors to chronic diseases such as cancer. It is of great value to identify the potential activity of various medicinal plants for regulating or blocking uncontrolled chronic inflammation. We investigated whether the root extract of Morus australis possesses antiinflammatory and antioxidative stress potential and hepatic protective activity. Methods: The microwave-assisted extractionwere was used to prepare the ethanol extract from the dried root of Morus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 30 publications
(31 reference statements)
3
4
0
Order By: Relevance
“…Notably, we found that flavonoids in A. conyzoides significantly decreased the serum levels of AST in mice, indicating that flavonoids in A. conyzoides have protective effects on hepatic function in mice. This is consistent with results in many previous researches that flavonoids could exert considerable protections against the hepatic damages induced by various causes [24,25].…”
Section: Agingsupporting
confidence: 93%
“…Notably, we found that flavonoids in A. conyzoides significantly decreased the serum levels of AST in mice, indicating that flavonoids in A. conyzoides have protective effects on hepatic function in mice. This is consistent with results in many previous researches that flavonoids could exert considerable protections against the hepatic damages induced by various causes [24,25].…”
Section: Agingsupporting
confidence: 93%
“…Meanwhile, an assessment of morusin influence on production of nitric oxide in the lipopolysaccharide-activated mouse macrophage RAW 264.7 cells carried out by Cheon et al [58] revealed that this compound efficiently suppressed iNOS enzyme induction at the concentration greater than 10 µM. Similar results were described by Tseng et al with regard to the liver protective effect of morusin [59].…”
Section: Anti-inflammatory Activitysupporting
confidence: 59%
“…These results indicate that there is a high correlation and regression between the phenolic contents and antioxidant potential of these extracts [10]. Ethanol extract from the dried root of M. australis (MRE) was also found to decrease CCl 4 -induced hepatic inflammation and necrosis in mice [92].…”
Section: Rootmentioning
confidence: 83%